Ecolinguistic-Based English for Computer Learning Tools to Develop Students’ Creative Thinking Ability - Indah Afrianti; Supriyaddin; Enung Nurhasanah; Asmedy; Nur Wahyuni (Jurnal Pendidikan dan Pengajaran, 2022)
Learning English is one of the important fundamental aspects that students must master from the lexicon/vocabulary learning process. Currently, lecturers only focus on giving assignments on test questions in general English books. This results in students not being confident in speaking English because they do not have a large collection of vocabulary. This study aims to produce an Ecolinguistic-based English for Computer learning tool. This research method is research development using the ADDIE model which consists of several steps, namely analysis, design, development, implementation, and evaluation. The subjects in this study consisted of 3 expert validation and 30 students in the information technology study program STKIP Yapis Dompu. The research instruments used in this research are Learning Device Validation Sheet, Learning Implementation Plan, Worksheet, Response Questionnaire, and Learning Outcome Test. The data analysis techniques in this study were expert validation analysis, test data analysis, and test analysis of learning outcomes. The result of this study shows learning tools of the material are presented well, the language used is easy to understand, and the questions given can be done by students. Textbooks are also effective in increasing the achievement of student learning outcomes because they are actively involved in finding material, finding relationships between materials, and being able to apply their knowledge so that students will be able to construct knowledge gained from their experiences. The resulting product is in the form of English course textbooks for students in the Information Technology Education Study Program.